PENGETAHUAN IBU BERHUBUNGAN DENGAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS KARANGAYU KOTA SEMARANG - Yuni Prihatin Ningtyas; Ari Udiyono; Nissa Kusariana (Jurnal Kesehatan Masyarakat (Undip), 2020)
According to toddler weigh operations in the city of Semarang, Karangayu is one of the health center with the highest number of stunting cases in Cemarang City, which is 16,7% in 2017. Stunted toddlers are at risk for growth failure, lowering children's IQ and worse, increasing the risk of infants suffering from non-communicable diseases. The purpose of this study was to analyze the factors associated with stunting in children under five years old in the working area of Karangayu Health Center, Semarang City. This study was an observational analytic study using a cross-sectional study design. The study was conducted in the working area of Karangayu Health Center in Semarang City from July - August 2019. The sample of the study was 115 mothers who have children under five years old in the working area of Karangayu Health Center. Statistical tests was using chi square with the results of factors related to stunting were history of chronic energy deficiency and level of nutritional knowledge. Meanwhile, unrelated factors are gender. Therefore, it can be concluded that the factors related to stunting in children under five years old in the working area of Karangayu Health Center in Semarang City were history of chronic energy and level of nutrition knowledge.